Hinein in neue Räume: Gedanken zur Bedeutung der Frage in der Hebräischen Bibel und im Jonabuch - Bergmann, Claudia D. (Biblische Zeitschrift, 2026)
The contribution presents the two conglomerates of questions in the Book of Jonah und discusses how these and other questions in the Hebrew Bible mark important passages in Scripture, speed up or slow down the story, increase the attention of the audience, and offer rooms for discussions and thinking in the minds of the intended readers. It concludes that the last sentence in the Book of Jonah should neither be marked as a question nor as an acclamation, maybe not even with a period ending the sentence. Its purpose is not to end the book but to allow for continuation of discussion.